Factors That Effect of the Optimal Plantlet Growth from Tissue Culture on the Acclimatization Stage - Irsyadi, Muhammad Burhanuddin (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Tissue culture is a method of propagation plants by isolating cell, tissues, protoplasts or plant organs than planting them in a sterile and controlled environment. This method is able to produce superior plants and propagation of plants are difficult to cultivate conventionally in large quantities with a relatively fast time. Acclimatization is an important final stage in the success of tissue culture method. Acclimatization is carried out for adaptation of the plantlet environment from in vitro to in vivo conditions. This is caused in the previous stage the plantlets are heterotrophic, while on acclimatization stage it will be autotrophic. This study aims to provide an information about the factors that affect the success of acclimatization plantlets. This is a review article was conducted using the literature study method by collecting information from journals, books or internet than analyzed in descriptive qualitative to prove scientifically. On this stage, many plantlets fail to grow and even die. for increase growth and reduce plantlets mortality need to be made overcome these problems. This can be overcome by applying acclimatization supporting factors. The result that factors affecting of the success plantlet growth on acclimatization stage including: the condition of the plantlets, light intensity, temperature, relative humidity, types of planting media, nutrition and fertilizing and controlling of pest and microorganisms.